2017
DOI: 10.1542/peds.2016-2624
|View full text |Cite
|
Sign up to set email alerts
|

How Does Incarcerating Young People Affect Their Adult Health Outcomes?

Abstract: BACKGROUND AND OBJECTIVES: Despite the widespread epidemic of mass incarceration in the US, relatively little literature exists examining the longitudinal relationship between youth incarceration and adult health outcomes. We sought to quantify the association of youth incarceration with subsequent adult health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 21 publications
0
106
1
2
Order By: Relevance
“…In a prior study using the National Longitudinal Study of Adolescent to Adult Health (Add Health) data, we found that young people's incarceration duration was associated with worse adult general health and higher rates of mobility limitations, depressive symptoms, and suicidal thoughts. 11 Other studies have similarly found any youth incarceration to be associated with worse adult general health, 11 higher rates of mobility limitations, 11 depressive symptoms, 11 obesity, 12 and hypertension and other stress-related illness. 13 Unfortunately, none of these studies, including our previous publication, have provided data to understand how incarceration of individuals during childhood compared to incarcerated at other young adult ages may be associated with their health outcomes in adulthood.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a prior study using the National Longitudinal Study of Adolescent to Adult Health (Add Health) data, we found that young people's incarceration duration was associated with worse adult general health and higher rates of mobility limitations, depressive symptoms, and suicidal thoughts. 11 Other studies have similarly found any youth incarceration to be associated with worse adult general health, 11 higher rates of mobility limitations, 11 depressive symptoms, 11 obesity, 12 and hypertension and other stress-related illness. 13 Unfortunately, none of these studies, including our previous publication, have provided data to understand how incarceration of individuals during childhood compared to incarcerated at other young adult ages may be associated with their health outcomes in adulthood.…”
Section: Introductionmentioning
confidence: 94%
“…For selecting the third category of covariates (i.e., other variables associated with incarceration and health), we applied an ecological framework 18 in reviewing relevant literature 7,13,19,20 to identify potential individual, family, and community-level factors potentially associated with both youth incarceration and health. Potential individual youthlevel covariates that we examined were: school connectedness (measured via 5-item scale, [Cronbach's alpha 0.83 21 ]; high-school grade point average (based on most recent grades) 11 ; perceived likelihood of attending college (measured via single-item 5-point scale); delinquent behaviors (measured via 12-item Serious Delinquency Scale, [Cronbach's alpha 0.81] 22 ); regular alcohol use (defined as drinking alcohol ≥2 days per month); cigarette use (defined as cigarette use once or more during the prior 30 days; marijuana use (defined as marijuana use at least once in the prior 30 days); and other drug use (defined as using "other drugs" such as cocaine once or more in the prior 30 days). Candidate family-level covariates were family household structure (categorized per Add Health as 2 biological parents, 2parent [≥1 non-biological], single parent, other); parental incarceration (measured via singleitem response); and family connectedness (measured via 3-item scale, Cronbach's alpha 0.77 23 ).…”
Section: Covariatesmentioning
confidence: 99%
“…These strategies may optimize developmental outcomes and reduce exposure to adverse events that dramatically alter the lived experiences, health, and perceived self-value of youth. 48,129,130 Optimizing Clinical Practice…”
Section: How Pediatricians Can Address and Ameliorate The Effects Of mentioning
confidence: 99%
“…Some mental health conditions directly contribute to youths’ propensity to offend or to be viewed as offenders, while other mental health conditions result from the incarceration and post-incarceration experiences endured by the youth 6 . Common mental health conditions in the juvenile justice population include attention-deficit/hyperactivity disorder, depression, anxiety, conduct disorder, and post-traumatic stress disorder (PTSD).…”
Section: Introductionmentioning
confidence: 99%